A comparison of the power of breathing sounds signals acquired with a smart stethoscope from a cohort of COVID-19 patients at peak disease, and pre-discharge from the hospital. (September 2022) - Kasim, Nour; Bachner-Hinenzon, Noa; Brikman, Shay; Cheshin, Ori; Adler, Doron; Dori, Guy
Highlights: COVID-19 pneumonia is difficult to detect if breathing sounds (BS) are normal. COVID-19 pneumonia BS contain distinct power in the infrasound range (<20 Hz). The infrasound frequencies cannot be sensed by the human ear. Power calculated over the infrasound range contributed 45% of all calculated power. Total power calculated from the right side of the back was increased during peak disease. Abstract: Objectives: To characterize the frequencies of breathing sounds signals (BS) in COVID-19 patients at peak disease and pre-discharge from hospitalization using a Smart stethoscope. Methods: Prospective cohort study conducted during the first COVID-19 wave (April-August 2020) in Israel. COVID-19 patients (n = 19) were validated by SARS-Cov-2 PCR test. The healthy control group was composed of 153 volunteers who stated that they were healthy. Power of BS was calculated in the frequency ranges of 0–20, 0–200, and 0–2000 Hz. Results: The power calculated over frequency ranges 0–20, 20–200, and 200–2000 Hz contributed approximately 45%, 45%, and 10% to the total power calculated over the range 0–2000 Hz, respectively. Total power calculated from the right side of the back showed an increase of 45–80% during peak disease compared with the healthy controls (p < 0.05). The power calculated over the back, in the infrasound range, 0–20 Hz, and not in the 20–2000 Hz range, was greater for the healthy controls than for patients. Using all 3 ranges of frequencies for distinguishing peak disease from healthy controls resulted in sensitivity and specificity of 84% and 91%, respectively. Omitting the 0–20 Hz range resulted in sensitivity and specificity of 74% and 67%, respectively. Discussion: The BS power acquired from COVID-19 patients at peak disease was significantly greater than that at pre-discharge from the hospital. The infrasound range had a significant contribution to the total power. Although the source of the infrasound is not presently clear, it may serve as an automated diagnostic tool when more clinical experience is gained with this method.